2000
DOI: 10.1177/154193120004402026
|View full text |Cite
|
Sign up to set email alerts
|

Driver Reaction Time in Crash Avoidance Research: Validation of a Driving Simulator Study on a Test Track

Abstract: A series of experiments was conducted on the Iowa Driving Simulator to examine driver reaction and performance in an intersection incursion crash scenario. To validate these simulator trials, a second study was run on a test track using a similar intersection incursion scenario to examine driver reaction and vehicle performance. Results showed that there was statistical equivalence between important driver reaction times with both studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 5 publications
3
78
0
1
Order By: Relevance
“…Therefore, there is a huge disparity in what is considered a "simulator." Subsequent examination of the data has shown that high fidelity simulators such as those at the University of Iowa, GE and others of similar complexity produce results that are very consistent with a "road" study, which is consistent with the findings of McGehee, Mazzae & Baldwin (2000).…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, there is a huge disparity in what is considered a "simulator." Subsequent examination of the data has shown that high fidelity simulators such as those at the University of Iowa, GE and others of similar complexity produce results that are very consistent with a "road" study, which is consistent with the findings of McGehee, Mazzae & Baldwin (2000).…”
Section: Discussionsupporting
confidence: 78%
“…Argument against human reaction time have been investigated and summarized in [7], and it is shown in their studies that reaction time to full braking are all around 2s obtained fro m regardless of simu lators or a test public road. The International Standards Organization [8] reports that maximu m permitted rate of decelerat ion is specified as 5m/s 2 , and longitudinal human-d riv ing braking is substantially less than the maximu m deceleration rate of 8.5m/s 2 even in the situation for crash avoidance or mitigation [9].…”
Section: Methodsmentioning
confidence: 99%
“…The latter time is below the American Association of State Highway and Transportation Officials' perception-brake response time of 2.5 s, which is used as an appropriate value for highway design. A study on crash avoidance was conducted in [35] comparing test track and simulator results for a sudden intersection crash scenario. The mean reaction time for releasing the throttle was 0.96 s in the simulator experiments and 1.28 s in the test track experiments.…”
Section: Reaction Timementioning
confidence: 99%